2013
DOI: 10.1080/14767724.2012.761811
|View full text |Cite
|
Sign up to set email alerts
|

PISA as an ideational roadmap for policy change: exploring Germany and England in a comparative perspective

Abstract: Education policy has undergone transformation in many countries over the last decade. In this article, we focus on the effects of the most significant international initiative in secondary education, which is the Organisation for Economic Cooperation and Development's (OECD) Programme for International Student Assessment (PISA). We analyse two countries that provide variation regarding the degree of change in their respective education policy-making due to this study; while Germany substantially reformed its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
0
12
0
2
Order By: Relevance
“…Contudo, os resultados e relatórios do PISA legitimaram a tomada de medidas políticas sobre os sistemas educativos, que foram consideradas por alguns governos, como por exemplo, os governos português, alemão e sueco. Esse subfator foi alvo de outros estudos na literatura internacional (DOBBINS;MARTENS, 2012;DOLIN;KROGH, 2010;EIJKELHOF;KOR-DES;SAVELSBERGH, 2013;KNODEL;NIEMANN, 2013;LUNDGREN, 2011;PONS, 2011).…”
Section: (V) Uso Das Tecnologias Da Informação E Comunicação (Tic)unclassified
“…Contudo, os resultados e relatórios do PISA legitimaram a tomada de medidas políticas sobre os sistemas educativos, que foram consideradas por alguns governos, como por exemplo, os governos português, alemão e sueco. Esse subfator foi alvo de outros estudos na literatura internacional (DOBBINS;MARTENS, 2012;DOLIN;KROGH, 2010;EIJKELHOF;KOR-DES;SAVELSBERGH, 2013;KNODEL;NIEMANN, 2013;LUNDGREN, 2011;PONS, 2011).…”
Section: (V) Uso Das Tecnologias Da Informação E Comunicação (Tic)unclassified
“…Even though different experiences from large scale studies have been described and discussed (Bulle, 2011;Grek et al 2009;Grek, 2009;Knodel, Martens, & Niemann, 2013;McGaw, 2004;Sellar & Lingard, 2013), using a large-scale methodology such as Allen suggested (Allen, 1994) has also led to other deaf education researchers following in his footsteps; see for example Convertino, Marschark, Sapere, Sarchet, & Zupan, 2009;Dammeyer, 2010;Luckner & Bowen, 2010;Qi & Mitchell, 2012. However, these studies do not report on such large cohorts as Grek reported PISA as having (Grek, 2009).…”
Section: Using Large-scale Methodsmentioning
confidence: 99%
“…Every week, there is one 6-8-hour day where lectures and seminars are tightly integrated. For every class, the students have independent reading and individual or group works to Grek (2009), Knodel, Martens, and Niemann (2013) Analysing messages of public debates (e.g media news) about PISA survey Analysis of the reactions to PISA and its importance in policy-making process and debates in a particular country prepare for the class, including site visits, interviews with stakeholders, following related media, etc. For the final examination, the students write the analysis of one relevant topic of educational policy in their national context, (1) evaluating the impact of this policy to concrete educational institution or learner or to the system in general, (2) describing how different stakeholders/interest groups could be involved in policy development and implementation, and (3) evaluating their personal possibilities to participate in policy debates as active citizens.…”
Section: Description Of the Module And Study Processmentioning
confidence: 99%